The Price of Secrecy: How Hiding Internal DRAM Topologies Hurts Rowhammer Defenses - Saroiu, Stefan; Wolman, Alec; Cojocar, Lucian (2022 International Reliability Physics Symposium, 2022)
DRAM vendors today choose to keep the internal topologies of DRAM devices secret. This decision introduces significant practical challenges for designers of memory controllers who wish to provide their own forms of Rowhammer defenses. This paper describes three such challenges and the vulnerabilities, inefficiencies, and overhead they introduce. Defenses implemented at the memory controller could reduce (if not eliminate) these deficiencies should internal DRAM topology be made available.